Maritime Digital Diplomacy: Legal Revitalization and Reform of Modern and Solutive Diplomacy - Birahayu, Dita (Audito Comparative Law Journal (ACLJ), 2023)
The existence of international politics and the foreign policy processes of a country has changed since the presence of the internet as a form of digitalization. The internet changed the practice of diplomacy and relations between countries. The Internet of Things is provided for all sectors. This also changes the dimension of diplomacy to digital diplomacy. Digital diplomacy cannot replace face-to-face diplomacy, but it still exists, and its needs will continue to increase. Digital diplomacy has also not been accommodated in the 1961 Vienna Convention on Diplomatic Relations, even though the development of diplomacy is very dynamic, along with the many disputes that arise between countries. Disputes between countries that often arise are disputes in the maritime sector. Therefore, maritime diplomacy is needed in resolving disputes in the maritime sector, considering that one of Indonesia's maritime axes. This research is normative juridical research that uses qualitative methods with statute and conceptual approach. The result of this research is that maritime digital diplomacy has a position as a means of communication and political negotiation, which is important for defending and fighting for national interests. Indonesia needs maritime digital diplomacy as a medium to fight for national interests and strategic issues in the maritime sector. A modern and solutive revitalization and legal reform of diplomacy is needed in order to establish good relations between countries.